Implementasi Kesetaraan Gender Wanita Kelas Atas dalam Sejarah Perjuangan Wanita Indonesia - Septiani Chairul Nisa (Pusat Studi Wanita dan Keluarga UGM, 2023)
Discussing gender cannot be separated from views that state human gender. In fact, this is not entirely true, gender does not only discuss which is male and which is female. Discussion of gender more than that can relate to customs, types of clothing, roles, habits or procedures, not forgetting also the instincts of the soul which can actually be carried out conditionally but are hindered by the view of the human position related to the nature he bears. Because that is what underlies the writing of this research journal. In writing this study the aims were to: (1) Know about gender equality, and (2) Knowing the history and forms of implementing the struggles of upper-class women from several eras in Indonesia.The research method used in this research is historical research method. The steps in historical research include: topic selection, heuristics, verification, interpretation, and historiography. The results of the research show that in the history and discussion of gender equality it does not only discuss the nature based on human sex but also the study of its meaning. Women are one of the objects discussed in gender equality. In this case, the role he played existed before modern times or the emancipation movement was echoed in various ways in its implementation. Regarding the realization, women who play a lot of roles are women from the upper class.